(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The study aims to identify the changes that occur in the reader’s eye movement when changing the layout methods of the inner pages of Arab newspapers. The study belongs to descriptive studies, and used the survey method, for a sample drawn using the available sample method for readers in the city of Damascus. The results of the study showed the variation of eye paths according to the layout methods used, and the design and layout of fixed and variable typographic elements together, and The photograph attracted attention in the first place, followed by the title in order, and a preference appeared for the right side of the page in accordance with the movement of the Arab reader’s eye, as the eye path moved from the location of the photograph (an element that attracts attention) directly towards the right side of the page, and the titles and newspaper articles located on the far right and left of the page obtained late ranks in the eye path, and multiple entrances to eye movement appeared on the studied pages according to the layout method used, which played a role in leading the eye movement in a manner consistent with the layout of the typographic elements on the page